REGENERATION AND TRANSPLANTATION OF CARTILAGE TISSUE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article reviews the latest advancements in cartilage tissue regeneration and transplantation. Cartilage damage, often resulting from trauma or degenerative diseases, represents a major clinical challenge due to the tissue’s limited capacity for self-repair. The paper discusses current therapeutic approaches, including surgical transplantation techniques and emerging regenerative medicine strategies. Special attention is given to biomaterials, stem cell applications, and tissue engineering technologies that aim to restore cartilage function and improve patient outcomes.